A tensed Tendyne. (25th April 2020) - Grinberg, Daniel; Pozzi, Matteo; Bernard, Chloé; Obadia, Jean-Francois
Abstract: We report a case of prosthesis dislodgement after transcatheter mitral valve replacement in an 85-year-old woman with chronic ischaemic heart failure. Two weeks after an initial successful implantation, she presented with a paravalvular leak associated with left ventricular outflow tract obstruction. Tether re-tensioning was performed and resolved the situation, but resulted in a deformation of the apical attachment zone into the left ventricle. Unfortunately, the patient finally expired from severe endocarditis. Proper anchoring is the main challenge for transcatheter mitral valve replacement techniques. Dislodgement of the prosthesis after transcatheter mitral valve replacement is an infrequent complication of the Tendyne ® procedure. This case emphasizes the importance of assessing the quality of the myocardium at the implantation zone of the apical pad, and of prosthesis oversizing, especially if low-profile valves are chosen. .